Bibliometric analysis of toll-like receptor agonists associated with cancer therapy. Issue 1 (7th January 2022) - Li, Wei; Wan, Li; Duan, Shaojun; Xu, Jingjing
Abstract: Background: Toll-like receptors (TLRs), a family of innate pattern-recognition receptors, have been exploited as a target for antitumor strategy. An increasing number of TLR agonists, serving as immunotherapeutics or vaccine adjuvants, were developed. This study aimed at exploring the status and trend of current researches on TLR agonists through bibliometric analysis. Methods: Original publications on TLR agonists were collected from the Web of Science Core Collection. Data were analyzed in terms of publication outputs, journals, countries, institutions, authors, co-authorship, co-citation, research hotspots, and evolution trends through VOSviewer and CiteSpace. Results: A total of 1914 TLR agonists-related articles, published in 612 academic journals between 2000 and 2019, were enrolled in the study. The Journal of Immunology published the most publications, followed by PLoS One and Blood . The USA that is in possession of the largest number of articles and the most extensive cooperators was the most leading country in this field. University of Minnesota ranked the first in terms of paper totality, but its average citations ranking was lower than University of Pennsylvania. Gudkov AV was the most productive author, whose team reported a TLR5 agonist that had radioprotective activity in mouse and primate models in 2008. The paper of Akira Shizuo, professor of Osaka University, was widely cited by international peers. The research trend of TLR agonists has undergone 3 periods: mechanisms of TLR signalings in immunotherapy (2000–2010), discovery of TLR agonists (2011–2014), application, therapeutic evaluation, and drug design of TLR agonists (2015–2019). Conclusion: This study provides investigators a landscape of TLR agonists research from the perspective of bibliometrics.